Is Ultrasonography More Sensitive Than Computed Tomography for Identifying Calcifications in Thyroid Nodules?. (1st October 2016) - Li, Jia-wei; Chang, Cai; Chen, Min; Zeng, Wei; Gao, Yi; Zhou, Shi-chong; Wang, Fen; Hu, Na; Chen, Ya-ling
Abstract : Objectives: The primary objective of this study was to evaluate the difference and agreement between ultrasonography (US) and computed tomography (CT) for identifying calcifications in thyroid nodules. Methods: Data from the medical records of 20, 248 patients were reviewed for preoperative diagnostic investigations and postoperative pathologic diagnoses. In total, 5247 records were selected for analysis based on the presence of calcifications reported in any of the following 3 modes: US, CT, and pathologic analysis. All 5247 patients underwent US examinations, whereas 3827 underwent cervical CT examinations. All patients had a postoperative pathologic diagnosis serving as a reference. The value of US for identification of calcifications and prediction of malignancy was analyzed on the basis of the entire cohort of 5247 records, whereas that of CT was based on 3827 records. The agreement between US and CT was analyzed on the basis of the 3827 common records. Results: Of the 5247 patients who underwent US, 4855 (92.5%) were found to have calcifications, whereas of the 3827 patients who underwent CT, 2040 (53.3%) were found to have calcifications ( P < .0005). Among the 404 cases with calcifications reported by pathologic analysis, the agreement rate between US and pathologic findings was significantly higher than that between CT and pathologic findings (87.9% versus 81.9%, respectively; P = .018). Conclusions: US is more sensitive and accurate than CT for detecting calcifications in thyroid nodules. Hence, US is recommended as the preferred imaging modality for calcification detection in thyroid nodules.